NIETZSCHE’S RECONSTRUCTION OF MORALITY VIS-À-VIS MORAL DECADENCE IN CONTEMPORARY NIGERIA: AN EXAMINATION (International Nexus Multidisciplinary Research Journal, 2026)
This study examines Nietzsche’s reconstruction of morality vis-à-vis moral decadence in contemporary Nigerian society. Nigerian contemporary society reflects a profound moral crisis, marked by deep-rooted corruption, hypocrisy as well as the disintegration of moral values. From a Nietzschean perspective, this moral decadence must be understood as the symptom of a deeper nihilism, the exhaustion of inherited ideals that no longer inspire vitality or creativity. Nietzsche’s pronouncement of the “death of God” symbolized the collapse of transcendent moral foundations; in much the same way, the Nigerian moral order rests on fragile conventions, often religious or cultural, that have lost their genuine authority. What is in vogue in contemporary Nigerian society is a morality of convenience, where weakness is translated as virtue, and self-interest hides beneath the language of communal good. The basic questions are: What are Nietzsche’s innovations in the domain of morality? What are the instances of moral decadence in contemporary Nigerian society? How can one interpret Nigerian moral crisis from Nietzschean point of view? What are the implications of Nietzsche’s reconstruction of morality on Nigerian society? These and other allied issues are given scholarly attention in this article. Employing the philosophical methods of analysis and phenomenology, this study examines moral decadence in Nigeria through the lens of Nietzsche’s moral philosophy. By unravelling the moral decadence that dominate Nigerian political, religious, and social dimensions of life, this study argues that the crisis is not merely institutional but existential. It is a crisis of meaning, wherein individuals and communities cling tenaciously to unacceptable and discredited values rather than daring to create new ones. The study advocates for a “revaluation of values,” urging Nigerians to embrace creativity, and responsibility in moral domain. Such a revaluation seeks to reconstruct morality on foundations capable of sustaining genuine human flourishing. This enables Nigerians to confront moral decadence, not with despair but with the possibility of renewal.